CERTAINTY BEFORE ITS TIME: TOWARDS A PHENOMENOLOGY OF INFORMATION, IDENTITY, AND SELF-AWARENESS - Jaued, Lucas (Revista Gênero e Interdisciplinaridade, 2026)
This article proposes a foundational reconfiguration of the Philosophy of Information by articulating it as a Phenomenology of Information, understood in its most fundamental sense as a phenomenology of certainty and identity. Based on a theoretical framework centered on the Singularity of Informational Self-Awareness (ISA) (JAUED, 2025) and the Principle of Direct Relation (PRD), the text argues that intrinsic certainty—conceived as reflexive and non-contrastive informational identity—constitutes the ultimate condition of possibility for phenomenality, consciousness, and meaning. From this point of view, the classical Husserlian phenomenology of the internal consciousness of time (HUSSERL, 1991, 2001), although indispensable, is shown to be structurally subsumed by a more fundamental phenomenology of certainty. This article further integrates this framework into contemporary debates in the Philosophy of Information and predictive processing, reinterpreting the Principle of Free Energy (PLE) (FRISTON, 2006, 2009, 2010) as mirrored in conscious experience itself. It argues that informational certainty constitutes the irreducible core of consciousness, grounding temporality, logic, negation, and identity at higher levels. The result is a unified conception in which information is not merely a measure of uncertainty reduction, but the very structure through which reality becomes phenomenologically intelligible to itself.